2011
DOI: 10.2174/157340611797928307
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of 2,3-Diarylated 2H-Benzo[e][1,2]Thiazine 1,1-Dioxides and their 3,4-Dihydro Derivatives, and Assessment of their Inhibitory Activity Against MCF-7 Breast Cancer Cells

Abstract: A practical synthesis of 2,3-diarylated 2H-benzo[e][1,2]thiazine 1,1-dioxides and their 3,4-dihydro derivatives was developed. ortho-Methyl lithiation of N-aryl-o-toluenesulfonamide followed by reaction with aryl aldehydes gave carbinol sulfonamides, which were either converted directly, or first oxidized to their ketones and converted, to 2,3-diarylated six-membered benzosultams via a TMSCl-NaI-MeCN mediated cyclization. A library of benzosultams was synthesized and evaluated for inhibitory activity against M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been shown that chemically modified 1,2-benzothiazine 1,1-dioxides are potent anti-inflammatory agents and their use does not correlate with ulcerogenicity occurrence [10]. In several studies, the chemopreventive, antioxidant and antimicrobial activity of the 1,2-benzothiazines was already shown [11][12][13]. In game-changing work by Soheili et al it was suggested that 1,2-benzothiazine-based drugs can be developed and used as potential inhibitors of the Pseudomonas aeruginosa, one of the most resistant and common opportunistic pathogen in nosocomial setting [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that chemically modified 1,2-benzothiazine 1,1-dioxides are potent anti-inflammatory agents and their use does not correlate with ulcerogenicity occurrence [10]. In several studies, the chemopreventive, antioxidant and antimicrobial activity of the 1,2-benzothiazines was already shown [11][12][13]. In game-changing work by Soheili et al it was suggested that 1,2-benzothiazine-based drugs can be developed and used as potential inhibitors of the Pseudomonas aeruginosa, one of the most resistant and common opportunistic pathogen in nosocomial setting [14].…”
Section: Introductionmentioning
confidence: 99%
“…Structural modification leading to improved chemical stability and pharmacological versatility is an essential medicinal approach to improve the bioavailability of lead compounds. Benzology is one of the often used approaches to derive new compounds with improved bioavailability and enhanced biological activity. , Intriguingly, several reports have revealed the potent biological activities of phthalazine derivatives obtained by benzology. For example, imidazole-based benzo­[ g ]­phthalazine derivatives were revealed to display potent leishmanicidal activity mediated by the inhibition of Leishmania Fe-superoxide dismutase (SOD) but not human CuZn-SOD. , For anticancer studies, the synthetic di- O -acetyl of (±)- cis -1,2-dihydroxy-1,2-dihydroacronycinebenzo­[ b ]­acronycine ( 6 ) was more potent than the corresponding di- O -acetate of the naturally occurring antitumor (±)- cis -1,2-dihydroxyacronycine ( 7 ) in inhibiting P388 leukemia and colon 38 adenocarcinoma in xenograft models .…”
Section: Introductionmentioning
confidence: 99%